Електричні і фотоелектричні властивості структур In/Cu0,92Zn0,08InS2 - Новосад, О. В.; Божко, В. В.; Герасимик, О. Р.; Novosad, О. V.; Bozhko, V. V.; Gerasymyk, O. R. (Східноєвропейський національний університет ім. Лесі Українки, 2011)
Методом термічного вакуумного напилення індію на поверхню тонких сколів монокристалів твердих розчинів CuInS2 ZnIn2S4 отримано фоточутливі структури In/n-Cu1-xZnxInS2 (x=0 0,16). Досліджено стаціонарні та світлові вольт-амперні характеристики одержаних структур. Обговорено механізми струмоперенесення і процеси фоточутливості.;Photosensitive structures of the In/n-Cu1-xZnxInS2 (x=0-0,16) have been prepared by the thermal vacuum deposition of indium on the surface of single crystals of solid solutions CuInS2-ZnIn2S4 thin chips. The stationary and light current-voltage characteristics of these structures are studied. The current mechanisms and the photosensitivity processes of the thin structures are being discussed.
Electrical and Рhotoelectrical Рroperties of the Sructures In/Cu0,92Zn0,08InS2
Keywords: тверді розчини; фоточутливі структури; вольт-амперна характеристика; коефіцієнт випрямлення; фотонапруга; solid solutions; photosensitive structures; current-voltage characteristics; rectification factor; photovoltage